Perbandingan Idiom yang Mengandung Bagian Tubuh Manusia pada Bahasa Arab dan Indonesia / The Comparison of Idioms Involving Human Body Parts in Arabic and Indonesian - Muhamad Fauzan Fauzi; Akmaliyah Akmaliyah; Dedih Wahyudin (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2025)
Idioms are small reflections of a society's culture, reflecting fundamental values and outlooks on life. This study aims to analyze the similarities and differences of idioms containing human body parts in Arabic and Indonesian. The research method used is a literature study with a contrastive analysis approach. The results of the study show similarities in the use of body metaphors to express abstract concepts in both languages, but there are differences in the selection of metaphors that reflect the influence of each cultural value. Arabic tends to use more symbolic and philosophical metaphors, while Indonesian is more pragmatic and concrete. This study concludes that idioms are not just expressions of language, but also reflections of a nation's culture. The results of this study are expected to contribute to the fields of linguistics, language teaching, and cross-cultural studies.المستخلص: التعابير الاصطلاحية هي تصور صغير لثقافة المجتمع، وتتصور القيم الأساسية ووجهات النظر حول الحياة. يهدف هذا البحث إلى تحليل أوجه التشابه والاختلاف في التعابير الاصطلاحية التي تحتوي على أجزاء جسم الإنسان في اللغة العربية والإندونيسية. طريقة البحث المستخدمة هي